1995
DOI: 10.1111/j.1532-5415.1995.tb05568.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Carbamazepine Toxicity in Frail Nursing Home Patients: A Controlled Study

Abstract: The findings indicate that carbamazepine in this dose range was well tolerated for the 5-week treatment period in this frail sample. These data supplement the literature regarding carbamazepine toxicity, which is devoid of controlled studies in older subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Thirtyseven publications were excluded for the following reasons: subjects not residents of nursing home (n = 8), publication not a research publication (n = 1), and trial occurred outside the United States (n = 28). The 45 publications in the final sample came from 21 journals 12–56 . These publications reported the following kinds of research: drug intervention 27% (12/45), care intervention 22% (10/45), device intervention 16% (7/45), physical or occupational therapy intervention 13% (6/45), assessment instrument 11% (5/45), patient or staff education 4% (2/45), behavior intervention 2% (1/45), diet intervention 2% (1/45), and electrolyte measurement 2% (1/45).…”
Section: Resultsmentioning
confidence: 99%
“…Thirtyseven publications were excluded for the following reasons: subjects not residents of nursing home (n = 8), publication not a research publication (n = 1), and trial occurred outside the United States (n = 28). The 45 publications in the final sample came from 21 journals 12–56 . These publications reported the following kinds of research: drug intervention 27% (12/45), care intervention 22% (10/45), device intervention 16% (7/45), physical or occupational therapy intervention 13% (6/45), assessment instrument 11% (5/45), patient or staff education 4% (2/45), behavior intervention 2% (1/45), diet intervention 2% (1/45), and electrolyte measurement 2% (1/45).…”
Section: Resultsmentioning
confidence: 99%
“…However, polypharmacy and comorbidities do not preclude the use of CBZ in the elderly. In a trial of frail elderly patients with dementia and agitated behaviours, the use of CBZ was well-tolerated and resulted in a reduction in the overall severity of patients' psychiatric symptoms [18,19]. Carbamazepine use is also not contraindicated for patients with hepatic dysfunction, although caution should be exercised when using CBZ to treat such patients, because CBZ metabolism takes place primarily in the liver [4].…”
Section: Special Populationsmentioning
confidence: 99%
“…A more recent confirmatory parallel group study of 6 weeks' duration in 51 patients also found a significant reduction in agitation using a mean dose of 300 mg/day [77]. Tolerability in these studies was generally good, with evidence of sedation and ataxia [78]; 8% subjects dropped out due to side effects in the larger confirmatory carbamazepine study. A 6-week, randomized, double-blind, placebo-controlled, parallel-group trial of carbamazepine 100 mg q.i.d.…”
Section: Anticonvulsantsmentioning
confidence: 79%
“…Side effects seen in other populations, such as rashes, sedation, hematologic abnormalities, hepatic dysfunction and altered electrolytes, would be more likely to be evident with widespread use of carbamazepine in the elderly [78]. Further, it has considerable potential for significant drug-drug interactions.…”
Section: Anticonvulsantsmentioning
confidence: 99%